Bede's Historiae: genre, rhetoric, and the construction of Anglo-Saxon church history - Gunn, Vicky (Boydell & Brewer, 2009)
A reappraisal of Bede's writings, focusing on his use of genre and rhetoric. The church history of the Anglo-Saxons can only be approached through the lens of a few writers, arguably the greatest of whom is Bede; his works illuminate an otherwise impoverished landscape of ecclesial development from conversion to established Christian church amongst the Anglo-Saxons. Bede, however, had his own agendas - monastic, political, and rhetorical. In her reappraisal of Bede's 'Ecclesiastical History, Lives of the Saints, History of the Abbots', the 'Lesser' and 'Greater Chronicles' and the 'Martyrology' and the audience for these texts, the author draws out the role played by classical forms of genre and rhetoric in the crafting of his work.She also explores the underlying political influences that caused Bede to write 'historia' as he did. In particular, she notes the role of 'historia' in monastic affairs, especially through the generation of a rhetoric of orthodoxy and the power of the cultural capital afforded by this within the relatively newly constituted Christian community in Northumbria. Dr VICKY GUNN is Senior Lecturer, Learning and Teaching Centre, University of Glasgow.